Next-Generation Smart Irrigation: A Fully Autonomous LoRa-Enabled Valve Controller with Multi-Year Battery Life - Haryono (AI Society & STMIK Indonesia, 2025)
Jagorawi Golf & Country Club currently relies on manual operation of its irrigation valves, a process that is labor-intensive and often inefficient. To address this, we introduce an automated valve-control system integrating LoRa long-range communication, motorized valves, and a 30,000 mAh battery designed to support remote operation through a smartphone or web interface. The system enables both manual remote control and fully automated scheduling while maintaining exceptional energy efficiency, achieving up to about 2 year of continuous operation without recharging. Power modeling incorporates two activity cycles: a 2-second cycle every 60 seconds drawing 50 mA for 0.8 s and 10 mA for the remaining time, and a daily 5-minute cycle consuming 1000 mA for the first second, decreasing linearly to 25 mA over the next 60 seconds, and stabilizing at 80 mA thereafter. Outside these operations, the device consumes only 1 mA in passive mode. The combination of low-power LoRa communication, optimized actuation profiles, and deep-sleep microcontroller strategies significantly reduces energy demands while improving reliability, consistency, and water-management efficiency over traditional human-operated systems.